SISTEMAS DE INTERAÇÃO E NAVEGAÇÃO EM LIVROS DIGITAIS: proposta de modelo de análise descritivo-normativo - LADEIRA, Felipe de Souza (2017)
The advent of the digital platform has given rise to a new form of narrative in the field of communication, characterized by the incorporation of dynamic elements such as audio, video and interactive infographics. However, the researches indicate the need for re-reading of the design with regard to the characterization and evaluation of digital books, as well as the strategic planning of the graphic interface, navigation process, interaction, inclusion of multimedia resources and analysis of user behavior . As a research question, how to structure interaction and navigation systems in digital books, this document presents the results of an exploratory-descriptive study that mapped the elements of interaction and navigation in digital books, and identified 40 recommendations for the design of digital books. Therefore, through the application of the descriptive-normative model, it was possible to prepare fourteen recommendations for the redesign of the digital book sample. The data identified by the model in the sample before and after the redesign, using different reading devices and applications, were compared and analyzed. It is concluded that the proposed model allows the redesign of digital books in a more objective and systematic way, contributing in the process of planning and development for digital books more dynamic and innovative.